2019
DOI: 10.1002/jsfa.9969
|View full text |Cite
|
Sign up to set email alerts
|

Allergenicity reduction and rheology property of Lactobacillus‐fermented soymilk

Abstract: BACKGROUND This study aimed to investigate the reduction in the potential allergenicity of soymilk, and its rheological properties, after fermentation with Lactobacillus. Soymilk (SM) was fermented with Lactobacillus brevis and Lactobacillus sp. The molecular weight of fermented soymilk (FSM) was characterized using sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS‐PAGE), and the potential allergenicity of FSM was analyzed using enzyme‐linked immunosorbent assay in vitro and the BALB/c mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…The treatment with fermented soybean induced reduction of mast cell protease-1 (mMCP-1) level and specific to soybean IgE, and boosted the secretion of IFN-γ [Yang et al, 2018]. Analogous results were reported by Xia et al [2019] in immunised BALB/c mice model get after the treatment with soy milk fermented only with LAB: Lactobacillus brevis CICC 23474 and Lactobacillus sp. CICC 23470 strains.…”
Section: Protein Bioavailability and Other Bioactive Effectssupporting
confidence: 64%
See 2 more Smart Citations
“…The treatment with fermented soybean induced reduction of mast cell protease-1 (mMCP-1) level and specific to soybean IgE, and boosted the secretion of IFN-γ [Yang et al, 2018]. Analogous results were reported by Xia et al [2019] in immunised BALB/c mice model get after the treatment with soy milk fermented only with LAB: Lactobacillus brevis CICC 23474 and Lactobacillus sp. CICC 23470 strains.…”
Section: Protein Bioavailability and Other Bioactive Effectssupporting
confidence: 64%
“…IgE, mMCP-1, and Th2-related cytokines were decreased, while IFN-γ production increased in spleen cell cultures. However, the intestinal villus was slightly damaged after the challenge [Xia et al, 2019], like in the Yang et al [2018] study.…”
Section: Protein Bioavailability and Other Bioactive Effectsmentioning
confidence: 59%
See 1 more Smart Citation
“…Boiling and autoclaving are common thermal technologies used to inactivate microorganism and anti-nutritional factors of food products with low cost and easy use [2,[8][9][10]. Many studies have demonstrated that the allergenicity of soybeans and peanuts were successfully reduced by boiling and autoclaving, respectively [6,[11][12][13][14]. Our previous study has also shown that the allergenicity of soybeans was decreased by boiling and autoclaving, resulting from the degradation of proteins and the changes in conformation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Among other treatments, unlike FSBM B , FSBM B+L had minimal upregulation of IL-6. After allergen protein was hydrolyzed by protease or fermentation, the lactic acid bacteria could reduce the peptides into a smaller size and increase their bioactivity [ 36 , 37 , 38 ]. Likewise, Ren [ 31 ] also indicated that soy peptide contains a large percentage of Glu and Asp that can down-regulate NF-κB , which causes an innate inflammatory response, and help repair the gut injury.…”
Section: Discussionmentioning
confidence: 99%